Optimal Contracting with Endogenous Social Norms - Fischer, Paul; Huddart, Steven (American Economic Review, 2008)
Research in sociology and ethics suggests that individuals adhere to social norms of behavior established by their peers. Within an agency framework, we model endogenous social norms by assuming that each agent's cost of implementing an action depends on the social norm for that action, defined to be the average level of that action chosen by the agent's peer group. We show how endogenous social norms alter the effectiveness of monetary incentives, determine whether it is optimal to group agents in a single or two separate organizations, and may give rise to a costly adverse selection problem when agents' sensitivities to social norms are unobservable. (JEL D23, D82, D86, Z13)